PES OF CORRECTIVE FEEDBACK USED BY FOUR LECTURERS ON STUDENTS’ SPEAKING PERFORMANCE - Silfia Rahmi (Politeknik Negeri Bengkalis, 2017)
Abstract: The objective of this study was to identify the types of corrective feedback used by the 4 lecturers in correcting students’ speaking performance This was descriptive research. The participants were 4 English lecturers who handled speaking class for the first year students at IAIN Batusangkar. Seven major types of corrective feedback which was initially conceived by Fanselowand is further developed by Lyster and Ranta, and Sheen and Yao become the grand theory in this study.The data were gathered by means of observation, video recording and guided interview. The observation and interview results demonstrate that of the seven types of the corrective feedback applied by the 4 lecturers on students’ speaking performance, recast feedback is the most frequently used. Most theories and previousfindings signify that it cannot locate the errors and it is not appropriate for EFL students. It is concluded that the type of corrective feedback that mostly used by the lecturers has not appropriate yet. That was estimated becomes the cause why the corrective feedback was not successful yet. It is recommended that those lecturers try to reconsider the type of corrective feedback which he or she frequently used since the appropriateness of type will influence the success of corrective feedback itself